Mulheres chefes de família num contexto beligerante: atuações femininas durante os conflitos fronteiriços na banda oriental (Rio Pardo 1811 a 1828) - Lopes, Lélia Coelho (2014)
This research examines the social relationships on the family´s context available in Rio Grande do Sul, a Captainship, after named the province of Rio Grande de São Pedro, in the locality of Rio Pardo, with a focus on women's situation during the military campaigns in the Banda Oriental (1811-1828). The border wars, typical in our space of study, and contributed to the formation / consolidation of South Rio Grande area, had influence in family formations due to the strategies and alliances established and constant military mobilizations of male troops, putting women in some positions that usually would be earmarked to male households components. By consulting bibliographies, funding requirements and Military Authorities of the Historical Archive of Rio Grande do Sul (AHRS), correspondences, petitions, letters, receipts of the Municipality of Rio Pardo (AHMRP), Varella´s Collection of documents and reports of travelers, We observed, in a qualitative manner, as the context of frontier and war have affected families in the region. We infer that the war situation did not allow the accommodation of family members into traditional social roles, since the absence of men because of the conflicts, has forced women to perform their duties. This research was conducted with funding Reuni/Capes and it is a part of the Integration, Policy and Frontier line research.